(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article highlights the importance of integrating, constantly changing and cooperating with employers theoretical and practical knowledge in the process of attesting masters of production education, based on foreign experience, and the fact that these approaches are an effective tool for effectively organizing the educational process and increasing the level of qualifications of masters of production education.